Meta-Analisis Pengaruh Bahan Ajar Fisika dan IPA Bermuatan Nilai Karakter Terhadap Hasil Belajar Siswa - Agustin, Silvia; Hanum, Siti Asma (Jurnal Penelitian Pembelajaran Fisika, 2021)
One of the goals of education related to character is that education must be able to instill character, that the function of education in Indonesia is to create human characters. Character education in students can be done through education, one of which is through teaching materials. Teaching materials that contain character values can make students master the targeted basic competencies. The type of research used in this study is a meta-analysis by testing 20 articles. This study analyzes and calculates the magnitude of the effect of teaching materials based on character values. Based on the results of the article analysis, it can be concluded that First, teaching materials with character have an effect on learning outcomes, especially the knowledge aspect with an effect size of 1.17. Both teaching materials with character are more effectively applied at the junior high school level with an effect size of 1.41 in the high category. Third, teaching materials with characters have a meaningful effect on the type of teaching material, namely student worksheets with an effect size of 1.55 high categories. Fourth, teaching materials with effective characters are used at the high school level, namely, dynamic electricity with an effect size of 1.78, while at the junior high school level with material / themes of straight motion; energy and effort; simple plane; style; Newton's Laws; pressure; atoms, ions and molecules with an effect size of 3.03 categories high.